Studies on Serum Creatinine and Creatinine Clearance in Hypertensive Patients - Sarkar, D; Latif, SA; Aich, J; Uddin, MM (Journal of Bangladesh Society of Physiologist, 2008)
Objectives: To assess the serum creatinine and creatinine clearance values in hypertensive patients for providing information to the health-policy planners, clinical practitioners about the importance of routine monitoring of serum creatinine and creatinine clearance in hypertensive patients for prevention of ESRD and other consequences to combat morbidity and mortality and to reinforce the need to consider these parameters in daily clinical practice. Study design: It was a cross-sectional study. Setting: The study was conducted at Department of Physiology and Biochemistry of Mymensingh Medical College, Medicine Unit of Mymensingh Medical College Hospital. Study period: The period of the study was January 2005 to December 2005. Participants: A total number of seventy subjects were included in this study. Out of 70 subjects, 40 (forty) were hypertensive patients and 30 (thirty) were normotensive & healthy controls. Intervention: The subjects were selected on the basis of history and clinical examination. Convenient sampling technique was applied. During visit the available hypertensive patients and controls (normotensive & healthy) those who were present were selected. Having received their written consent they were interviewed & examined by prepared personal data sheet and sample of blood (after overnight fasting) was drawn for biochemical examination. Main outcome measure: Mean values of serum creatinine and creatinine clearance. Result: Serum creatinine was greater in hypertensive than those of normotensive. Creatinine clearance was less in hypertensive than those of normotensive. Serum creatinine & creatinine clearance in between males hypertensive & control shows that CrCl were statistically significant but not the serum creatinine. In females of hypertensive & control shows no differences in case of SCr & CrCl. Among 40 hypertensive the number of Getting treatment - regular & Getting treatment-irregular was 14 (35%) & 26 (65%) respectively. Similarly in patients suffering less than 5 yrs and suffering 5 yrs & above the differences are also not statistically significant. Conclusion: The observations of this study revealed that most of the hypertensive patients were taking treatment irregularly and there was significant alteration of biochemical parameters in hypertensive patients. Therefore, for routine monitoring of hypertensive patients to prevent the end stage renal disease (ESRD) and other consequences, the reinforcement of the investigations of these parameters may be recommended in daily clinical practice.Key Words: Hypertension, creatinine, creatinine clearance, Cockcroft-Gault formulaJ Bangladesh Soc Physiol. 2006 Dec;(1):19-26.